The Role of 3D Reconstruction True-Volume Analysis in Osteochondral Lesions of the Talus: A Case Series. (September 2018) - Walley, Kempland C.; Gonzalez, Tyler A.; Callahan, Ryan; Fairfull, Aubree; Roush, Evan; Saloky, Kaitlin L.; Juliano, Paul J.; Lewis, Gregory S.; Aynardi, Michael C.
Background: Evaluation and management of osteochondral lesions of the talus (OLTs) often warrant advanced imaging studies, especially in revision or cases with cystic defects. It is possible that orthopedic surgeons may overestimate the size and misinterpret the morphology of OLT from conventional computed tomography (CT), thereby influencing treatment strategies. The purpose of this study was to determine the utility of a novel means to estimate the true-volume of OLTs using 3D reconstructed images and volume analysis. Methods: With Institutional Review Board approval, an institutional radiology database was queried for patients with cystic OLTs that failed previous microfracture, having compatible CT scans and magnetic resonance imaging (MRI) between 2011 and 2016. Fourteen patients met inclusion criteria. Of these, 5 cases were randomly selected for 3D CT reconstruction modeling. Ten orthopedic surgeons independently estimated the volume of these 5 OLTs via standard CT. Then 3D reconstructions were made and morphometric true-volume (MTV) analysis measurements of each OLT were generated. The percent change in volumes from CT were compared to MTVs determined from 3D reconstructive analysis. Results: On average, the volume calculated by conventional CT scanner grossly overestimated the actual size of the OLTs. The volume calculated on conventional CT scanner overestimated the size of OLTs compared to the 3D MTV reconstructed analysis by 285% to 864%. Conclusions: Our results showed that conventional measurements of OLTS with CT grossly overestimated the size of the lesion. The 3D MTV analysis of cystic osteochondral lesions may help clinicians with preoperative planning for graft selection and appropriate volume while avoiding unnecessary costs incurred with overestimation. Level of Evidence: Level IV, case series.